The relationship between employment with labour productivity, capital productivity and output of small and medium sized enterprise (SME) in manufacturing industry / Norzila Othman - Othman, Norzila (2007)
The purpose of this study is to determine the relationship between employment with labour productivity, capital productivity and output of Small and Medium Sized Enterprise (SME) in Manufacturing Industry. This study includes data from year 2002-2006. For this purpose all the data will be analyze using the correlation analysis to see the relationship between each variable. The data that being used in this study is the growth performance of employment, labour productivity, capital productivity and output of Small and Medium Sized Enterprise (SME) and concentrated on the manufacturing industry. For data analyzing, this study used SPSS to get the result. Based on the analysis only capital productivity that have a significant relationship with employment.